The challenges of diagnosing glaucoma in myopic cases and the important role of Bruch's membrane opening-minimum rim width in the diagnosis of myopic glaucoma - Gökhan Çelik; Murat Sinan Saricaoğlu (Photodiagnosis and Photodynamic Therapy)
Background: Glaucoma is a progressive neurodegenerative disease that can lead to blindness; furthermore, axial myopia is associated with retinal and optic nerve changes that mimic glaucoma. Diagnosing glaucoma in myopic eyes is challenging due to anatomical variations, emphasizing the need for precise OCT-based evaluations. Objective: To evaluate the retinal nerve fiber layer (RNFL) thickness and Bruch's Membrane Opening-Minimum Rim Width (BMO-MRW) parameters in myopic patients with and without glaucoma by using Spectralis® optical coherence tomography (OCT), in order to reveal the relationship between axial length (AL) and OCT parameters and also to determine the OCT parameters that should be considered when diagnosing glaucoma in myopic cases. Material and method: This prospective and cross-sectional study included 95 eyes from 95 cases. There were a total of 54 patients over 40 years of age without any systemic disease or glaucoma, and 41 patients without any systemic disease but with mild or moderate glaucoma, according to the Hodapp staging system. Optical biometry using the Lenstar® 900 and Heidelberg Engineering Spectralis® OCT Glaucoma Module Premium Edition (GMPE) with an anatomic positioning system (APS) were performed on all patients, along with a full ophthalmological examination. The cases were divided into subgroups according to the AL results of optical biometry as short (<24 mm) and long (≥24 mm). The measurement results were recorded and compared statistically. Results: A total of 54 healthy subjects consisting of 27 with short AL and 27 with long AL were included. In the glaucoma group, 20 out of 41 subjects had short AL, while 21 had long AL. Using measurements in GMPE mode with APS, no statistically significant difference was found between the eyes with the short and long AL in the healthy group, both in terms of global RNFL thickness and BMO-MRW analyses. In the glaucoma group, there was no statistically significant difference between eyes with short and long AL in terms of RNFL and MRW analyses. In the myopic group, the highest AUC value of the RNFL measurements in different circular scans of the GMPE module was found in the inferotemporal area. Using the GMPE software with the APS to measure RNFL thickness, in particular in the inferotemporal quadrant, together with the BMO-MRW, really helped to make a definite diagnosis of glaucoma in myopic patients. Conclusion: In conclusion, utilizing GMPE with APS in the diagnosis of glaucoma provides accurate outcomes in myopic cases. The RNFL thickness and BMO-MRW values of the inferotemporal quadrant are particularly valuable in diagnosing glaucoma in myopic patients.